Overcoming Environmental Risks to Achieve Sustainable Development Goals Lessons from the Japanese Experience - Nakajima, Tamie; Nakamura, Keiko; Nohara, Keiko; Kondoh, Akihiko; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This thought-provoking book examines how the accumulated knowledge on past and present environmental issues and risks within Japan can be applied in order to help deliver the transformation to a sustainable and well-being society. The book opens with a series of case analyses on environmental pollution events and pollution-related diseases within the country over the past half century or more. Lessons learned regarding the harm to society are highlighted. Diverse current environmental issues are then explored in detail, ranging from the management of hazardous chemical and asbestos exposure to marine plastic pollution and nuclear disasters. This discussion forms the basis for the final part of the book, which focuses on how progress can be made towards the Sustainable Development Goals set out in the United Nations$1 (B2030 Agenda for Sustainable Development. Important insights are also provided into future directions in human ecology and ecotoxicology. The book will be a valuable resource for both new and established researchers as well as for those seeking comprehensive information on environmental/occupational health and health promotion.s
1 Purpose of This e-Book -- Part 1 Learning from Case Analysis of Past Environmental Risks -- 2 Minamata Disease -- 3 Itai-Itai Disease: Health issues caused by environmental exposure to cadmium and residents$1 (Bfight to rebuild the environment in the Jinzu River Basin in Toyama -- 4 Arsenic intoxication in Toroku district of Japan -- 5 Yokkaichi asthma: Health effects of air pollutants in Japan -- 6 Environmental Policy and International Environmental Cooperation Learned from the YOKKAICHI Air Pollution -- 7 What We Have Learned from the Pollution that Occurred in Japan a Half Century Ago -- Part 2 Environmental Issues That the World Is Watching Now -- 8 Current Status and Problems Concerning the Management of Persistent Or-ganic Chemicals Used in Products and those of Unintentional Products in Japan -- 9 Health risk assessment and management of asbestos exposure to the public in Japan -- 10 Marine plastic pollution: chemical aspects and possible solutions -- 11 Solution and Agreement in the Nuclear Disaster: Toward an Inclusive Society Respecting Relationship from Sacrificial System -- 12 Current environmental risks and their management in Japan -- Part 3 Towards the Realization of a Sustainable and Well-Being Society -- 13 The Future of Washing -- 14 Initiatives On Responsible Consumption$1 (BOguni Town -- 15 From Court Decisions on Pollution to Targets of Future Actions -- 16 An Initiative of an Environmental Model City: Featuring Sustainable and Healthy Cities -- 17 Divorcing from plastics for a sustainable future society -- 18 Issues of environmental risks in the Anthropocene -- 19 Spectrum of Environmental Risk -Assessment, Management and Communication.s
Keywords: Medicine, Industrial; Environmental health; Toxicology; Occupational Medicine; Environmental Health; Toxicology; Environmental Health; Sustainable Development